2015
DOI: 10.1111/apa.12970
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis is more severe in children over the age of two who have an increased body mass index

Abstract: These data suggest that the severity of atopic dermatitis is associated with increased BMI percentile in children older than 2 years, although this association was not apparent in younger ages using weight for length. Our results indicate the need for new avenues in the prevention and treatment of these entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(29 reference statements)
2
12
0
Order By: Relevance
“…Yao and colleagues also found that a high BMI is associated with a higher prevalence of atopic eczema in a group of patients aged 4–18 years. Other authors have also reported that elevated BMI is associated with more severe AD …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Yao and colleagues also found that a high BMI is associated with a higher prevalence of atopic eczema in a group of patients aged 4–18 years. Other authors have also reported that elevated BMI is associated with more severe AD …”
Section: Discussionmentioning
confidence: 89%
“…Other authors have also reported that elevated BMI is associated with more severe AD. [16][17][18][19] A key strength of our study is that the diagnosis of AD and classification of disease severity were established by dermatologists and paediatricians by direct observation of individual patients and by scoring using the SCORAD index. This methodology contrasts with that of previous studies, including the ISAAC study, in which AD severity was assessed using questionnaires administered to parents.…”
Section: Bmi and Damentioning
confidence: 99%
“…Atopic dermatitis and obesity In general, recent studies have found that prevalence of AD is positively associated with obesity, overweight or high BMI. The studies are based on doctor-diagnosed AD, 37,[43][44][45][46][47] and few studies adjust for possible confounders. 43,48,49 Older studies have not been able to find this association.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of the positive association of obesity with AD in children and adults (203031). Similar to our results, in a nation-wide study of 5,202 Korean adults, obesity was positively related to the presence of AD in women (20).…”
Section: Discussionmentioning
confidence: 99%